PEMILIHAN KATA TERJEMAHAN SYAIR PADA BUKU FIHI MA FIHI KARYA JALALUDDIN RUMI - Putri Budikurnia Istiqomah; Rohanda Rohanda (Jurnal Bastra (Bahasa dan Sastra), 2025)
Translating a book can help many people access its content in a language they understand. However, translation often involves challenges, particularly with sentences that are not easily comprehensible to readers. This is especially true for poetry, which frequently employs figurative language and metaphors. In this case, the author applies Newmark's translation methods to analyze the poetry in the book Fihi Ma Fihi by Jalaluddin Rumi, which has been translated from Arabic into Indonesian by Anwar Holid. The research method used in this study is descriptive qualitative, focusing on the verses of poetry within the book. Translators often rely on various translation theories, which sometimes result in ambiguous diction. The translator determines the translation method based on the context of the poetry and its linguistic nuances. Anwar Holid's translation incorporates idiomatic expressions and styles of human communication, influencing both the conveyed meaning and the reader's understanding. This study examines the shifts in meaning at a lexical level and the translator's choices in rendering Rumi's poetry. Eleven stanzas are analyzed in terms of their translations and compared to their lexical meanings. Each word carries a distinct meaning and translation that aligns with the poetic verses written by Jalaluddin Rumi.